2016
DOI: 10.1080/14764172.2016.1197402
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioma treatment with pulsed dye laser—distinct parameters used between neonatal and non-neonatal patients

Abstract: PDL, with distinct parameters, was effective in the treatment of IHs in neonates. After each laser treatment, neonates recovered faster than non-neonatal patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…The efficacy and safety of laser treatment in dermatology was completely improved in 1983 due to the introduction of the selective photothermolysis theory by Anderson and Parrish[36]. Numerous studies have confirmed the efficacy of PDL treatment, especially for the treatment of superficial IHs[37,38]. However, it was not very effective for thick/deep IHs, because of the limited penetration of the laser.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of laser treatment in dermatology was completely improved in 1983 due to the introduction of the selective photothermolysis theory by Anderson and Parrish[36]. Numerous studies have confirmed the efficacy of PDL treatment, especially for the treatment of superficial IHs[37,38]. However, it was not very effective for thick/deep IHs, because of the limited penetration of the laser.…”
Section: Discussionmentioning
confidence: 99%
“…(1) IH that meets the relevant diagnostic criteria in the Guidelines for the Diagnosis and Treatment of Hemangiomas and Vascular Malformations in 2019; 22 (2) B-ultrasound manifested the thickness of the IH is greater than 2mm and less than or equal to 8mm; (3) The child has not received other treatments before diagnosis and treatment; (4) Children with multiple lesions were excluded. (5) Children with skin lesions on the scalp, eyelids and perineum were excluded. A total of 78 children with IH were collected, including 21 males (26.9%) and 57 females (73.1%), with an age of (4.5 ± 1.4) months (range 22 days to about 6 months).…”
Section: Methodsmentioning
confidence: 99%
“…At present, laser treatment of superficial IH is mainly based on pulsed dye laser (PDL) (wavelength 585 nm or 595 nm) and the non-selective β-blocker timolol. [4][5][6] According to the existing literature, IH > 2 mm is regarded as thicker IH. [7][8][9] However, PDL has insufficient penetration depth for thicker IH, so the treatment result is not ideal.…”
Section: Introductionmentioning
confidence: 99%
“…Laser treatment is not recommended during the proliferative phase of IH growth [20,64,65] due to a lack of effectiveness and the risk of potential complications [66]. However, Zhang et al showed that the use of PDL in neonates requires less energy and reduces recovery time between sessions compared to non-neonates [67]. Laser treatment plays a significant role in treating residual lesions, such as telangiectasia [64].…”
Section: Mechanism Of Actionmentioning
confidence: 99%